1000 DEG C-resistant high-toughness high-temperature wear-resistant alloy, preparation method thereof and alloy part

The development of a high-strength, high-temperature wear-resistant alloy with optimized composition and carbide distribution addresses the limitations of existing materials, providing enhanced wear resistance and mechanical properties for service up to 1050℃.

CN119663058AInactive Publication Date: 2025-03-21GAONA AERO MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411924324.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Current high-temperature wear-resistant materials fail to meet the increasing demands for temperature resistance and comprehensive mechanical properties, particularly at temperatures above 1000℃, due to inadequate wear resistance, strength, and compressive performance, which limits their service life in high-temperature environments such as aerospace engine components.

Method used

A high-strength, high-temperature wear-resistant alloy composed of Cr 15-25%, W+Mo 5-12%, Nb 11-20%, Ti 0-4%, C 1-3%, Fe 0.1-5%, Al 0.5-5%, Hf+Y 0.1-3%, with the remainder being Co, is developed, featuring a γ-Co-based solid solution with dispersed carbides like MC, M23C6, and M6C, optimized for uniform distribution and size to enhance mechanical properties.

Benefits of technology

The alloy exhibits superior wear resistance, strength, and comprehensive mechanical properties, enabling stable service at temperatures from 1000 to 1050℃, with improved micro-oxidation resistance and reduced risk of cracking, significantly outperforming existing materials in high-temperature applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663058A_ABST
    Figure CN119663058A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high-temperature wear-resistant materials, in particular to a 1000 DEG C-resistant high-toughness high-temperature wear-resistant alloy, a preparation method thereof and an alloy part. The 1000 DEG C-resistant high-toughness high-temperature wear-resistant alloy comprises the following components in percentage by mass: 15%-25% of Cr, 5%-12% of W + Mo, 11%-20% of Nb, 0%-4% of Ti, 1%-3% of C, 0.1%-5% of Fe, 0.5%-5% of Al, 0.1%-3% of Hf + Y and the balance of Co. Through reasonable design of the alloy components, the alloy has the characteristics of high use temperature, good obdurability, excellent high-temperature fretting wear performance and comprehensive mechanical property and the like, and can stably serve for a long time at the high temperature of 1000-1050 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high temperature wear-resistant materials, and in particular to a 1000°C resistant high strength and toughness high temperature wear-resistant alloy and a preparation method and alloy parts thereof. Background Art

[0002] With the development of the wear protection field in recent years, the requirements for the temperature resistance and comprehensive mechanical properties of high-temperature wear-resistant materials in certain service environments have been further improved. Take the surface wear-resistant strengthening of aircraft engine turbine blade crowns with wear-resistant materials as an example. Since the turbine blade crowns are subjected to the continuous action of multiple alternating loads during operation, there is micro-wear, extrusion and vibration between adjacent working surfaces. This unique working condition requires not only excellent wear resistance, but also good toughness and compression resistance to ensure that no serious deformation and cracking occurs during the blade crown extrusion process. And with the development of the aviation industry, the service temperature of turbine blade crowns is getting higher and higher, reaching 1000℃, which places higher and higher requirements on the temperature resistance of blade crown wear-resistant materials.

[0003] At present, high-temperature wear-resistant materials are mainly composed of metal matrix and dispersed hard reinforcement phase particles. The service temperature can reach up to 950℃, but not more than 1000℃. This is mainly because these materials have insufficient wear resistance and toughness at high temperatures. With the development of the field of high-temperature wear protection, the service environment above 1000℃ will face the problem of no materials available. Therefore, it is of great significance to develop high-temperature wear-resistant materials with good service wear resistance, toughness, compression resistance and excellent comprehensive mechanical properties, and can be used above 1000℃.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One object of the present invention is to provide a high-strength, high-temperature wear-resistant material having excellent 1000°C high-temperature wear resistance, toughness, compression resistance and comprehensive mechanical properties, and can serve in a 1000°C high-temperature environment.

[0006] Another object of the present invention is to provide a method for preparing a high-strength, high-toughness, high-temperature wear-resistant material that can withstand 1000°C.

[0007] Another object of the present invention is to provide an alloy part made of the above-mentioned high-strength, high-toughness and high-temperature wear-resistant material that can withstand 1000°C.

[0008] In order to achieve the above-mentioned purpose of the present invention, on the one hand, the present invention provides a high-strength, tough and high-temperature wear-resistant alloy resistant to 1000°C, which includes, by mass percentage, Cr 15% to 25%, W+Mo 5% to 12%, Nb11% to 20%, Ti 0% to 4%, C1% to 3%, Fe 0.1% to 5%, Al 0.5% to 5%, Hf+Y0.1% to 3%, and the balance is Co.

[0009] In a specific embodiment of the present invention, in the 1000° C. high-strength, high-toughness, high-temperature wear-resistant alloy, the mass percentage of W is 5% to 10%; the mass percentage of Mo is 0% to 4%.

[0010] In a specific embodiment of the present invention, in the 1000° C. high-toughness and high-temperature wear-resistant alloy, the mass percentage of Hf is 0.4% to 2.6%; the mass percentage of Y is 0.04% to 0.1%.

[0011] In a specific embodiment of the present invention, in the 1000° C. high-strength, high-toughness, high-temperature wear-resistant alloy, the mass percentage of C is 1.2% to 2.3%.

[0012] In a specific embodiment of the present invention, in the 1000° C. high-strength, high-toughness, high-temperature wear-resistant alloy, the mass percentage of Al is 1% to 3%.

[0013] In a specific embodiment of the present invention, the 1000° C. high-strength, high-toughness, high-temperature wear-resistant alloy comprises a γ-Co-based solid solution and carbides dispersed in the γ-Co-based solid solution.

[0014] In a specific embodiment of the present invention, the carbide includes MC, M 23 C 6 and M 6 C. Furthermore, in the alloy, the volume fraction of the carbide is ≥15%.

[0015] In a specific embodiment of the present invention, the volume fraction of MC is 15% to 25%. 23 C 6 The volume fraction of M is 0.1% to 3%. 6 The volume fraction of C is 0.1% to 4%.

[0016] In a specific embodiment of the present invention, the average size of the carbide is 10-40 μm. Furthermore, the maximum size of the carbide is less than 50 μm.

[0017] Another aspect of the present invention provides a method for preparing any one of the above-mentioned high-strength, high-toughness and high-temperature wear-resistant alloys resistant to 1000°C, comprising the following steps: preparing raw materials according to the alloy composition, and performing vacuum induction melting and casting.

[0018] Another aspect of the present invention provides an alloy part made of any one of the above-mentioned high-strength, high-toughness, high-temperature, wear-resistant alloys resistant to 1000°C.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention reasonably designs the alloy composition so that the alloy has the characteristics of high operating temperature, good toughness, high temperature fretting wear resistance and excellent comprehensive mechanical properties, and can be in long-term stable service at high temperatures of 1000-1050°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 The typical microstructure of the high-strength, high-toughness, high-temperature, wear-resistant alloy provided in Example 3 of the present invention;

[0023] Figure 2 The typical microstructure of the high-strength, high-toughness, high-temperature, wear-resistant alloy provided in Example 5 of the present invention;

[0024] Figure 3 Fretting wear curves of the alloys provided in Example 3, Example 5 and Comparative Example 4 of the present invention at 850°C;

[0025] Figure 4 Comparison of fretting wear curves of the high-strength, high-toughness, high-temperature wear-resistant alloy provided in Example 5 of the present invention at 850°C and 900°C;

[0026] Figure 5 The displacement-time variation curves of the alloys provided in Example 3, Example 5 and Comparative Example 4 of the present invention during compression at 1000°C / 200MPa for 10 minutes;

[0027] Figure 6 Appearance of the samples of the alloys provided in Example 3, Example 5 and Comparative Example 4 of the present invention after being compressed at 1000°C / 200MPa for 10 minutes;

[0028] Figure 7 Appearance of the samples of the alloys provided in Example 3, Example 5 and Comparative Example 4 of the present invention after being compressed at 1050°C / 200MPa for 10 minutes;

[0029] Figure 8The appearance of the samples of the alloys provided in Example 5 of the present invention and Comparative Example 4 at similar compression rates. DETAILED DESCRIPTION

[0030] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0031] At present, high temperature wear-resistant alloys mainly include Stellite6 and Tribaloy-800 (T800) alloys developed in the United States and ΒКHA-2M alloys developed in Russia. Stellite6 alloy is based on γ-Co and M 7 C 3 or M 6 C-type carbide is a hard reinforcing phase with a service temperature below 700°C. T800 alloy has a volume fraction of 40% to 60% Laves phase (CoMoSi and CoMo 2 Si) as the hard reinforcement phase, with a cobalt-based solid solution containing Cr and Mo elements as the matrix. Compared with Stellite 6 alloy, T800 alloy has higher hot hardness and better wear resistance, and the maximum service temperature is 850℃. 3 Al-based alloy is the matrix, with about 20% (volume fraction) β-NiAl phase and trace carbide phase as hard reinforcement phase. Its high-temperature micro-wear resistance is 4 to 6 times that of T800 alloy, and the maximum service temperature can reach 950°C. The service temperature of high-temperature wear-resistant alloys at this stage does not exceed 1000°C. On the one hand, the friction coefficient of existing high-temperature wear-resistant alloys increases with increasing temperature, resulting in poor wear resistance at high temperatures, which limits its service at higher temperatures. On the other hand, in order to ensure the hardness and wear resistance of the alloy, high-temperature wear-resistant alloys have certain requirements for the number and volume fraction of wear-resistant hard phases. The content of wear-resistant hard phases in existing high-temperature wear-resistant alloys is relatively high, the size is large, and the size distribution is uneven. For example, the skeleton-like M in Stellite6 alloy 7 C 3The length of the carbide is about 25μm, the maximum size of the blocky Laves phase in the T800 alloy reaches about 75μm, and the minimum size does not exceed 10μm. The present invention has found that these wear-resistant hard phases are all hard and brittle phases with poor toughness and plasticity, and cracks are more likely to occur around the larger hard phases. Due to the unreasonable size distribution of wear-resistant hard phases in existing wear-resistant alloys, the toughness and plasticity at high temperatures are poor, the alloy's compression resistance is poor, and it is easy to crack or even collapse when squeezed, which seriously limits its service at higher temperatures.

[0032] The present invention selects suitable hard reinforcing phase and metal matrix, the reinforcing phase bears the main wear stress during service, the metal matrix bears the role of supporting the reinforcing phase, coordinating deformation and bearing impact stress, and the matrix and the reinforcing phase have good thermodynamic compatibility and physical coexistence, good wettability and strong interface bonding force. At the same time, the morphology, size and distribution of the reinforcing phase are regulated by adjusting the alloy composition to ensure the wear resistance of the material.

[0033] Based on this, on the one hand, the present invention provides a high-strength, tough and high-temperature wear-resistant alloy resistant to 1000°C, which includes, by mass percentage, Cr 15% to 25%, W+Mo 5% to 12%, Nb 11% to 20%, Ti 0% to 4%, C 1% to 3%, Fe 0.1% to 5%, Al 0.5% to 5%, Hf+Y 0.1% to 3%, and the balance is Co.

[0034] The present invention reasonably designs the alloy composition, so that the alloy has the characteristics of high use temperature, good toughness, high temperature fretting wear resistance and excellent comprehensive mechanical properties, and can be used stably for a long time at a high temperature of 1000-1050°C. Wherein, W+Mo refers to the sum of the mass percentages of W and Mo, and Hf+Y refers to the sum of the mass percentages of Hf and Y.

[0035] Compared with Ni-based alloys, Co has a lower friction coefficient and better wear resistance; at the same time, Co is a low stacking fault energy metal, and stacking faults and nano twins are easily formed in the γ-Co matrix, which is conducive to further improving the wear resistance of the alloy. Elements such as W and Mo added to the γ-Co matrix can play a good solid solution strengthening role, which can improve the strength of the matrix and improve the mechanical properties of the alloy. Therefore, the present invention selects γ-Co based solid solution as the matrix.

[0036] The Nb used in the alloy of the present invention is a strong carbide forming element, and MC-type carbide NbC can be formed in the Co-based alloy. In addition to the characteristics of high hardness, the basic physical parameters of NbC, such as Young's modulus and thermal expansion coefficient, are relatively close to those of the Co matrix, and it is not easy to cause the bonding force between NbC and the matrix to decrease due to thermal stress at high temperature; at the same time, NbC has a stable crystal form, is easy to precipitate in the metal matrix, is not easy to grow in size, and can present a uniform dispersion distribution. Based on these advantages of NbC in the Co matrix, NbC can effectively strengthen the alloy and bear the main wear stress in the wear-resistant material. Further research has found that increasing the Nb content can increase the volume fraction of the NbC hard phase in the alloy, and improve the hardness and wear resistance of the alloy. However, the oxidation activation energy of the Nb element is low, and in-situ oxidation is easy to occur after the formation of NbC. Too high a content of NbC is not conducive to the high-temperature oxidation resistance of the alloy; at the same time, as a hard and brittle phase, too high a content of NbC will also lead to reduced plasticity and toughness of the alloy. Therefore, the mass percentage of the Nb element in the alloy of the present invention is controlled to be 11% to 20%. For example, in different embodiments, the mass percentage of the Nb element in the alloy can be 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any two thereof.

[0037] The C element in the alloy of the present invention can promote the formation of carbides and mainly participates in the formation of MC, M 23 C 6 and M 6 C three types of carbides. Adjusting the mass percentage of C element in the range of 1% to 3%, combined with other components, is more conducive to ensuring the morphology, size, distribution, etc. of the carbides. For example, in different embodiments, the mass percentage of C element in the alloy can be 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3% or any two thereof.

[0038] The Al element in the alloy of the present invention has an important influence on the oxidation resistance of the alloy. The content of Al element has an important influence on the Al content of the protective oxide film. 2 O 3 Increasing the Al content can promote the formation of dense and stable Al on the surface of the alloy during high temperature oxidation. 2 O 3The Al content is too high to form a CoAl phase which is detrimental to the high temperature strength of the alloy. Therefore, the mass percentage of the Al element in the alloy of the present invention is 0.5% to 5%. For example, in different embodiments, the mass percentage of the Al element in the alloy can be 0.5%, 1%, 1.5%, 2%, 2.5%, 2.8%, 3%, 3.5%, 4%, 4.5%, 5% or any two of them.

[0039] The Cr element in the alloy of the present invention is also beneficial to the high temperature oxidation resistance of the alloy and can promote the formation of the protective oxide film Cr. 2 O 3 At the same time, the simultaneous addition of Al and Cr elements can promote the formation of Al 2 O 3 Nucleation and shortening to form continuous Al 2 O 3 The time required for the film to form, thereby synergistically improving the oxidation resistance of the alloy. In addition, the Cr element can also promote the 23 C 6 and M 6 The formation of C carbides, thereby further increasing the content of carbides in the alloy. However, too high a Cr content can easily lead to an excessive content of Cr-rich carbides, which are more likely to transform and decompose at high temperatures, affecting the high-temperature structural stability of the alloy. Therefore, the present invention regulates the mass percentage of the Cr element in the alloy to be 15% to 25%. For example, in different embodiments, the mass percentage of the Cr element in the alloy can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or a range consisting of any two of them.

[0040] The W and Mo elements in the alloy of the present invention are important solid solution strengthening elements in Co-based high-temperature alloys, which can improve the strength of the alloy matrix. In addition, the W and Mo elements can also form carbides to increase the content of hard phases in the alloy, thereby improving the wear resistance of the alloy. The present invention regulates the sum of the mass percentages of W and Mo to be 5% to 12% to take into account the strength, wear resistance and compression resistance of the alloy. For example, in different embodiments, the sum of the mass percentages of W and Mo can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12% or a range consisting of any two of them.

[0041] The addition of trace elements Hf and Y in the alloy of the present invention can improve the high-temperature oxidation resistance of the alloy. Hf has a higher affinity with O. Hf segregated at the grain boundary combines with O to inhibit the migration of metal cations and has an inhibitory effect on the growth of the oxide film. During the oxidation process, the segregation of harmful elements (such as S) will occur at the oxide film / matrix interface. When the concentration of S element at the interface reaches saturation, it will further diffuse into the oxide film through the oxide film / matrix interface and enter the oxide film grain boundary, which is detrimental to the oxidation resistance of the alloy. The Hf element can inhibit the segregation of harmful elements at the oxide film / matrix interface, reduce the internal stress of the oxide film, and improve the bonding force between the oxide film and the matrix, thereby effectively reducing the oxidation rate of the alloy. When the Y element exists, the Hf element can more effectively play the role of inhibiting the segregation of harmful elements at the oxide film / matrix interface. Therefore, the sum of the mass percentages of Hf and Y in the alloy of the present invention is 0.1% to 3%. For example, in different embodiments, the sum of the mass percentages of Hf and Y may be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or a range consisting of any two thereof.

[0042] Co undergoes an FCC→HCP allotropic transformation at about 417°C. Adding a certain amount of Fe element to the alloy of the present invention can stabilize the γ-Co crystal form, thereby ensuring the stability of the alloy matrix. For example, in different embodiments, the content of Fe element in the alloy can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range consisting of any two of them.

[0043] Ti element is also a forming element of TiC of MC type carbide, and the hardness of TiC is very high, second only to diamond. Ti element can be further added to the alloy of the present invention to promote the formation of (Nb, Ti) C together with Nb element, so as to further improve the hardness and wear resistance of the alloy. However, too high Ti element content is also likely to cause the high temperature oxidation resistance of the alloy to decrease. Therefore, the mass percentage of Ti element in the alloy of the present invention is 0% to 4%. For example, in different embodiments, the mass percentage of Ti element in the alloy can be 0%, 1%, 1.5%, 2%, 2.5%, 2.8%, 3%, 3.5%, 4% or a range consisting of any two of them.

[0044] The alloy of the present invention uses a γ-Co based solid solution as a matrix, uses NbC as a main hard reinforcement phase, and combines M formed by Cr, W, and Mo elements. 23 C 6 and M 6 C-type carbide, through MC, M 23 C 6 and M 6 C and other carbide hard phases for composite strengthening.

[0045] In a specific embodiment of the present invention, in the 1000° C. high-toughness and high-temperature wear-resistant alloy, the mass percentage of W is 5% to 10%; the mass percentage of Mo is 0% to 4%.

[0046] For example, in different embodiments, the mass percentage of W can be 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two thereof; the mass percentage of Mo can be 0%, 0.5%, 1%, 2%, 3%, 4% or a range consisting of any two thereof.

[0047] In a specific embodiment of the present invention, in the 1000° C. high-toughness and high-temperature wear-resistant alloy, the mass percentage of Hf is 0.4% to 2.6%; the mass percentage of Y is 0.04% to 0.1%.

[0048] For example, in different embodiments, the mass percentage of Hf can be 0.4%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.3%, 2.6% or a range consisting of any two thereof; the mass percentage of Y can be 0.04%, 0.05%, 0.06%, 0.08%, 0.1% or a range consisting of any two thereof.

[0049] In a specific embodiment of the present invention, in the 1000° C. high-strength, high-toughness, high-temperature wear-resistant alloy, the mass percentage of C is 1.2% to 2.3%.

[0050] In a specific embodiment of the present invention, in the 1000° C. high-strength, high-toughness, high-temperature wear-resistant alloy, the mass percentage of Al is 1% to 3%.

[0051] In a specific embodiment of the present invention, the high-toughness and high-temperature wear-resistant alloy with a resistance to 1000° C. includes a γ-Co-based solid solution and carbides dispersed in the γ-Co-based solid solution. In the alloy of the present invention, carbides are the main precipitation phases.

[0052] In a specific embodiment of the present invention, the carbide includes MC, M 23 C 6 and M 6 C. Furthermore, in the alloy, the volume fraction of carbides is ≥ 15%.

[0053] In a specific embodiment of the present invention, in the alloy, the volume fraction of carbides is 15% to 35%.

[0054] For example, in different embodiments, in the alloy, the volume fraction of carbides may be 15%, 20%, 25%, 30%, 35%, or a range consisting of any two thereof.

[0055] In a specific embodiment of the present invention, the volume fraction of MC is 15% to 25%, and M 23C 6 The volume fraction is 0.1% to 3%, M 6 The volume fraction of C is 0.1% to 4%.

[0056] The volume fraction of NbC rich in Nb element can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or a range consisting of any two thereof; the volume fraction of NbC rich in Cr and W elements (Cr, W) ... 23 C 6 The volume fraction of W can be 0.1%, 0.5%, 1.0%, 1.5%, 2%, 2.5%, 3% or any two thereof; W rich in W 6 The volume fraction of C can be 0.1%, 0.5%, 1.0%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or a range consisting of any two thereof.

[0057] In the alloy of the present invention, the total volume fraction of carbides is regulated within the above range, and NbC is the main component, which is evenly dispersed and presents block or granular form with reasonable size. There are no carbides with large size or abnormal growth along a certain orientation. This organizational feature ensures the wear resistance of the alloy on the one hand, and the cooperative deformation ability between the wear-resistant hard phase and the matrix on the other hand, avoiding the initiation of cracks around large-sized carbides, so that the alloy can have good strength and toughness.

[0058] In a specific embodiment of the present invention, the average size of the carbide is 10-40 μm, for example, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm or any two thereof. Further, the maximum size of the carbide is less than 50 μm, for example, less than 40 μm, less than 35 μm, less than 30 μm, etc.

[0059] The carbides of the present invention have uniform sizes, and the maximum size is controlled within a certain range, such as 45 μm, 39 μm, 38 μm, 36 μm, 33 μm, 31 μm, 30 μm, 28 μm, 26 μm, 25 μm, 22 μm, 20 μm or a range consisting of any two of them, thereby avoiding the initiation of cracks around the hard phase and improving the strength and toughness of the alloy.

[0060] Another aspect of the present invention provides a method for preparing any one of the above-mentioned high-strength, high-toughness, high-temperature wear-resistant alloys resistant to 1000°C, comprising the following steps: preparing raw materials according to the alloy composition, and performing vacuum induction melting and casting.

[0061] The raw materials of each element in the alloy composition can be as follows, but are not limited thereto, for example, electrolytic cobalt, metallic chromium, metallic niobium, sponge titanium, metallic aluminum, metallic tungsten, metallic molybdenum, pure iron, crystalline hafnium, metallic yttrium, graphite, etc. can be used as raw materials.

[0062] The present invention provides a specific preparation method, but is not limited thereto. Vacuum induction melting may include: according to the alloy composition, electrolytic cobalt, metal chromium, metal niobium, metal tungsten, metal molybdenum, and pure iron are placed in a crucible of a vacuum induction melting furnace, and other elements are added from a hopper; in a medium frequency induction vacuum melting furnace, low-power electricity is first supplied for 10 minutes to remove hydrogen, and then high-power electricity is supplied until the whole is melted, and refining begins, the refining temperature is 1550-1600°C, the refining is 10-45 minutes, and the vacuum degree during the refining is less than 5Pa; after the refining is completed, graphite is added, and the temperature is lowered to 1450°C±10°C after melting, and metal aluminum, sponge titanium, crystalline hafnium and metal yttrium are added in sequence, and after melting, high-power stirring is performed to evenly mix, and pouring is performed when the temperature of the molten steel is controlled to be 1500-1550°C.

[0063] Another aspect of the present invention provides an alloy part made of any one of the above-mentioned high-strength, high-toughness, high-temperature and wear-resistant alloys resistant to 1000°C.

[0064] In a specific embodiment of the present invention, the alloy component may include but is not limited to a blade crown wear block.

[0065] Examples 1 to 7

[0066] Examples 1 to 7 respectively provide high-strength, high-toughness, high-temperature wear-resistant alloys capable of withstanding 1000°C and preparation methods thereof. The composition of the high-strength, high-toughness, high-temperature wear-resistant alloys capable of withstanding 1000°C is shown in Table 1.

[0067] The preparation method of the high-strength and high-toughness high-temperature wear-resistant alloy resistant to 1000°C comprises the following steps:

[0068] (1) Electrolytic cobalt, metallic chromium, metallic niobium, sponge titanium, metallic aluminum, metallic tungsten, metallic molybdenum, pure iron, crystalline hafnium, metallic yttrium, and graphite are selected as raw materials, and the raw materials are weighed according to the actual composition of the alloy and set aside for use.

[0069] (2) Electrolytic cobalt, metallic chromium, metallic niobium, metallic tungsten, metallic molybdenum, and pure iron are placed in a crucible of a vacuum induction melting furnace, and other elements are added from a hopper.

[0070] (3) Melting is carried out in a medium frequency induction vacuum melting furnace. First, low power is supplied for 10 minutes to remove hydrogen, and then high power is supplied until it is fully melted, and refining begins. The refining temperature is 1570-1580°C, and the refining time is 30 minutes. The vacuum degree during refining is <5Pa. After refining is completed, graphite is added, and the temperature is lowered to 1450°C±10°C after melting. Metal aluminum, sponge titanium, crystalline hafnium and metal yttrium are added in turn. After melting, high power is used to stir evenly, and pouring is carried out when the temperature of the molten steel is controlled to be 1530-1540°C.

[0071] Table 1 Compositions of different 1000℃ high-toughness and high-temperature wear-resistant alloys (wt%)

[0072] serial number Al Cr Nb Ti W Hf Y Mo C Co Example 1 1 25 14 0 9.5 2.5 0.04 0 2.2 Remain Example 2 1.5 20 12 2 9.5 1.5 0.04 0 1.8 Remain Example 3 2 20 15 0 9.5 0.5 0.04 0 1.85 Remain Example 4 2 20 16 0 6 0.5 0.04 3 1.85 Remain Example 5 2 20 11 4 9.5 0.5 0.04 0 1.85 Remain Example 6 2.5 15 11 4 6 1.0 0.04 3 1.8 Remain Example 7 3 15 18 0 6 1.5 0.04 0 1.5 Remain

[0073] Comparative Examples 1 to 3

[0074] Comparative Examples 1 to 3 provide high temperature alloys and preparation methods thereof, respectively. The preparation methods are the same as those in Example 1, except that the compositions of the high temperature alloys are different. The compositions of the high temperature alloys of Comparative Examples 1 to 3 are shown in Table 2.

[0075] Table 2 High temperature alloy composition of different comparative examples (wt%)

[0076]

[0077]

[0078] Comparative Example 4

[0079] Comparative Example 4 provides a high-temperature alloy ΒКHA-2M alloy, comprising the following components in mass percentage: Cr 5%, Al 10.3%, Ti 1.3%, W 2%, Si 1.05%, C 0.18%, and the balance is Ni.

[0080] Experimental example

[0081] Figure 1 and Figure 2 The typical microstructures of the high-strength, high-toughness, high-temperature wear-resistant alloys provided in Examples 3 and 5 of the present invention are shown in Figure 1. The light grey phase is carbide, and the dark grey phase is γ-Co matrix. As can be seen from the figure, the high-strength, high-toughness, high-temperature wear-resistant alloys in the embodiments of the present invention use γ-Co solid solution as the matrix. 23 C 6 and M 6 The typical microstructures of the alloys of each embodiment and comparative example were further characterized, and the MC, M 23 C 6 and M 6 The volume fraction and size of C carbides are shown in Table 3.

[0082] Table 3 Volume fraction and average size of precipitated phases in different alloys

[0083]

[0084] The alloys of the embodiments of the present invention and the comparative examples were tested for high-temperature fretting wear performance. The high-temperature fretting wear test was conducted on a German high-temperature fretting wear tester SRV-4, with the following test conditions: test cycle 15min, frequency 50Hz, amplitude 0.2mm, load 200N, test temperature 850℃ / 900℃, and body wear was used. Table 4 shows the fretting wear volume and stable period friction coefficient of the alloys of the embodiments of the present invention and the comparative examples at 850℃ and 900℃. Figure 3 is the fretting wear curve of the alloys of Example 3, Example 5 and Comparative Example 4 at 850°C, Figure 4 The fretting wear curves of the alloy of Example 5 of the present invention at 850°C and 900°C are compared.

[0085] Table 4 Fretting wear volume and stable friction coefficient of different alloys at 850℃ and 900℃

[0086]

[0087] After fretting at 850°C, the wear volume of the alloys in the embodiments of the present invention does not exceed 2.4×10 6 μm 3 , which is significantly smaller than the alloy of Comparative Example 4 (2.81×10 6 μm 3 The friction coefficient of the alloys in the embodiments of the present invention does not exceed 0.45, which is more than 10% lower than that of the alloy in comparative example 4. Figure 3 It can be seen that the fretting wear curve of the alloy of the embodiment of the present invention is smoother and the friction coefficient fluctuates less over time. Figure 4 It can be seen that after fretting at 900°C, the friction coefficient of the alloy in the embodiment of the present invention does not exceed 0.25 during the stable period, which is lower than the friction coefficient at 850°C, indicating that as the temperature increases, the wear resistance of the alloy in the embodiment of the present invention is further improved, showing a certain self-lubricating effect. The fretting wear volume and friction coefficient of the alloys in Comparative Examples 1 to 3 of the present invention at 850°C and 900°C are significantly higher than those of the alloy in the embodiment of the present invention.

[0088] It can be seen from the above test results that the alloy of the embodiment of the present invention has excellent high-temperature fretting wear performance and has certain self-lubricating properties at high temperatures.

[0089] The high temperature compression performance test was conducted on the alloys of the embodiments of the present invention and the comparative examples. Table 5 shows the compression ratios of the alloys of the embodiments of the present invention and the comparative examples after compression at 1000°C and 1050°C. Figure 5 The displacement-time curves of the alloys of Example 3, Example 5 and Comparative Example 4 of the present invention during compression at 1000°C / 200MPa for 10 minutes are shown in FIG. Figure 6 The appearance of the samples of the alloys of Example 3, Example 5 and Comparative Example 4 of the present invention after being compressed at 1000°C / 200MPa for 10 minutes. Figure 7 This is the appearance of the samples of the alloys of Example 3, Example 5 and Comparative Example 4 of the present invention after being compressed at 1050°C / 200MPa for 10 minutes.

[0090] Table 5 Compression ratio of different alloys after compression at 1000℃ and 1050℃ for 10 min under different loads (%)

[0091]

[0092] It can be seen from Table 5 that the compression resistance of the alloy of the embodiment of the present invention at different load levels of 1000℃ and 1050℃ is significantly better than that of the alloy of Comparative Example 4. From the perspective of compression rate, the compression resistance of the alloy of the embodiment of the present invention at 1000℃ / 200MPa is about 3.5 times that of the alloy of Comparative Example 4, and the compression resistance at 1050℃ / 200MPa is about 2 times that of the alloy of Comparative Example 4. Figure 5 It can be seen that after being compressed at 1000℃ / 200MPa for 10 minutes, the compression amount of the alloy of comparative example 4 increases significantly with time, while the compression amount of the alloys of Examples 3 and 5 of the present invention changes slowly with time, and is smaller than that of the alloy of comparative example 4, indicating that the alloys of Examples 3 and 5 of the present invention have better compression resistance. Figure 6 and Figure 7 : The appearance of the compressed samples (the original dimensions of the samples in each embodiment and the comparative example are consistent) more intuitively demonstrates the compression resistance advantage of the alloys in the embodiments of the present invention. After compression at 1000°C / 200MPa and 1050°C / 200MPa for 10 minutes, the alloy sample of comparative example 4 is severely deformed, and obvious compression cracks appear on the surface, while the deformation of the alloy samples of embodiments 3 and 5 of the present invention is significantly smaller than that of the alloy of comparative example 4, and there are no cracks on the surface.

[0093] Further, the alloy samples of Example 5 and Comparative Example 4 were subjected to compression tests at the same level of compression ratio (the compression ratio of the alloy of Example 5 was 64.4%, and the compression ratio of the alloy of Comparative Example 4 was 69.75%). Figure 8 The appearance of the samples of the alloys provided in Example 5 of the present invention and Comparative Example 4 at similar compression rates. Figure 8It can be seen that the alloy of comparative example 4 cracked obviously, while the surface of the alloy of example 5 remained unchanged, which further illustrates that the alloy of example 5 of the present invention has better toughness and can remain intact under a larger deformation. The compression rates of the alloys of comparative examples 1 to 3 of the present invention under different loads at 1000°C and 1050°C are significantly higher than those of the alloys of the present invention.

[0094] It can be seen from the above test results that the alloys of the embodiments of the present invention have excellent high-temperature compression resistance and toughness, and have very significant advantages over existing materials.

[0095] High temperature tensile and high temperature rupture performance tests were performed on the alloys of the embodiments of the present invention and the comparative examples. The test results are shown in Tables 6 and 7.

[0096] Table 6 Tensile properties of different alloys at 900℃ and 1000℃

[0097]

[0098] Table 7 High temperature durability of different alloys

[0099]

[0100] As can be seen from Tables 6 and 7, the tensile strength of the alloys of the embodiments of the present invention at 900°C and 1000°C is at a similar level to that of the alloys of Comparative Example 4, but the tensile plasticity is significantly higher than that of the alloys of Comparative Example 4, and the tensile elongation at 900°C is more than 4 times that of the alloys of Comparative Example 4, and the tensile elongation at 1000°C is more than 3 times that of the alloys of Comparative Example 4. In addition, the alloys of the embodiments of the present invention have a long-lasting life of more than 150 hours at 900°C / 100MPa, with the longest reaching 202 hours, which is 3 to 4.5 times that of the alloys of Comparative Example 4; and a long-lasting life of more than 120 hours at 1000°C / 50MPa, with the longest reaching 173 hours, which is 20 to 35 times that of the alloys of Comparative Example 4. In addition, the long-lasting plasticity of the alloys of the embodiments of the present invention is also significantly better than that of the alloys of Comparative Example 4, and the long-lasting elongation at 900°C and 1000°C is more than 2 times that of the alloys of Comparative Example 4. This indicates that the alloy of the present invention embodiment has significantly better toughness at high temperature than the alloy of comparative example 4. The high temperature tensile strength, tensile plasticity, high temperature endurance life and endurance plasticity of the alloys of comparative examples 1 to 3 of the present invention are all lower than those of the alloy of the present invention embodiment.

[0101] From the above test results, it can be seen that the alloy of the embodiment of the present invention not only has the characteristics of high high temperature strength and long lasting life, but also has very excellent plasticity and toughness. It is a high temperature wear-resistant alloy with good strength and toughness and excellent comprehensive mechanical properties.

[0102] In summary, the high-strength and high-temperature wear-resistant alloy of the present invention has high strength and toughness and excellent wear resistance, and is a high-temperature wear-resistant alloy that can serve in a high-temperature environment of 1000-1050°C.

[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. High-strength and high-temperature wear-resistant alloy resistant to 1000℃, characterized in that: Calculated by mass percentage, it includes: Cr 15% to 25%, W+Mo 5% to 12%, Nb 11% to 20%, Ti 0% to 4%, C 1% to 3%, Fe 0.1% to 5%, Al 0.5% to 5%, Hf+Y 0.1% to 3%, and the balance is Co.

2. The 1000°C high-toughness high-temperature wear-resistant alloy according to claim 1 is characterized in that: The mass percentage of W is 5% to 10%; the mass percentage of Mo is 0% to 4%.

3. The 1000°C high-toughness high-temperature wear-resistant alloy according to claim 1, characterized in that: The mass percentage of Hf is 0.4% to 2.6%; the mass percentage of Y is 0.04% to 0.1%.

4. The 1000°C high-toughness high-temperature wear-resistant alloy according to claim 1, characterized in that: Having at least one of the following characteristics: (1) The mass percentage of C is 1.2% to 2.3%; (2) The mass percentage of Al is 1% to 3%.

5. The 1000°C high-toughness high-temperature wear-resistant alloy according to claim 1, characterized in that: The 1000°C high-toughness high-temperature wear-resistant alloy comprises a γ-Co based solid solution and carbides dispersed in the γ-Co based solid solution; The carbides include MC, M 23 C6 and M6C.

6. The 1000°C high-toughness high-temperature wear-resistant alloy according to claim 5, characterized in that: In the alloy, the volume fraction of the carbide is ≥15%.

7. The 1000°C high-toughness high-temperature wear-resistant alloy according to claim 5, characterized in that: The volume fraction of the MC is 15% to 25%, and the M 23 The volume fraction of C6 is 0.1% to 3%, and the volume fraction of M6C is 0.1% to 4%.

8. The 1000°C high-toughness high-temperature wear-resistant alloy according to claim 5, characterized in that: The average size of the carbide is 10 to 40 μm; The maximum size of the carbides is <50 μm.

9. The method for preparing the 1000°C high-toughness high-temperature wear-resistant alloy according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: preparing raw materials according to alloy composition, and performing vacuum induction melting and casting.

10. An alloy part, characterized in that: It is made of the 1000°C resistant high-strength, high-toughness, high-temperature wear-resistant alloy described in any one of claims 1 to 8.